Cultural Perceptions, Emotional Intelligence, and Conflict Resolution Abilities of High School Students: A Study on the Influence of Ghanaian Traditional Culture - Amedome, Sedem Nunyuia; Kartadinata, Sunaryo; Ilfiandra; Suherman, Uman (Jurnal Pendidikan dan Pengajaran, 2024)
Significant gaps in understanding perceptions of traditional Ghanaian culture affect secondary school students' emotional intelligence and conflict resolution skills. This study was conducted to analyze the influence of conventional Ghanaian culture on students' perceptions of their own culture, as well as how it impacts their emotional intelligence and conflict resolution skills in the school setting. To assess these relationships, the study utilized a quantitative research design with partial least squares structural equation modeling. The study targeted a diverse sample of 674 students aged 16-18 from various educational institutions. The data collection method used was a questionnaire. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM). The findings showed that emotional intelligence significantly mediated the relationship between perceptions of traditional culture and conflict resolution skills. This study emphasizes integrating cultural elements into the educational framework to enhance conflict resolution skills. The implications of this study include actionable recommendations for educators and policymakers to develop culturally responsive strategies to encourage more effective conflict management in schools.